Implementasi Toleransi Umat Beragama : Telaah Hubungan Islam dan Kristen di Durensewu Pasuruan Jawa Timur - Arifin, Achmad Zainul (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
ABSTRACT Islam and Christianity are religions that have a long history in the life of social communities in Indonesia. The pairs of relations between the two religions have been going on for a long time. Conflict there are several regions in Indonesia that are related to social harmony with various supporting factors that exist in the community. This research will support how the pattern of participation of Islam and Christian minorities, as well as the field of harmony that unites the social relations of the two religions. Then this study is a qualitative study using observation techniques and direct interviews to the field to collect data with research objects. The results of this study suggest that both in Islam and Christianity are related to good relations within a religious and social framework. Furthermore, in building social relations that are found in several religious harmony fields, the yard is a place of worship, a village spring, a village hall and a village field. Keywords: Islam, Christianity, Tolerance, and social harmony.